Weekday-weekend variations in mother-/father-child physical activity and screen time relationship: a cross-sectional study in a random sample of Czech families with 5- to 12-year-old children - Sigmundová, Dagmar; Bucksch, Jens (European journal of sport science, 2018)
This study assessed the associations between these factors in a random sample of Czech families with preschool and school-aged children. A nationally representative sample comprised 185 families with preschool children and 649 families with school-aged children (dyads; both parents and child n = 365, mother and child n = 730, and father and child n = 469). The participants wore Yamax Digiwalker SW-200 pedometers at least four weekdays and both weekend days and completed family logbooks (anthropometric parameters, daily step counts (SC), and screen time (ST)). When a parent (fathers at weekends and mothers both on weekdays and at weekends) achieved 10,000 SC per day, their children were also significantly (OR = 2.93-6.06, 95% CI = 2.02-9.26) more likely to meet the daily SC recommendation. On the contrary, the involvement of fathers in organized leisure-time PA reduced their children's odds of meeting the SC recommendation on weekdays (OR = 0.53, 95% CI = 0.31-0.89) and at weekends (OR = 0.41, 95% CI = 0.24-0.72). The excessive ST of parents at weekends reduced the odds of their children meeting the SC recommendation (mother-child dyads: OR = 0.44, 95% CI = 0.26-0.72; father-child dyads: OR = 0.63, 95% CI = 0.37-1.06). High levels of parents’ PA contribute to the achievement of the recommended daily PA in children on weekdays and at weekends. Excessive weekend ST of parents reduces their odds of their children achieving the recommended daily PA; however, the influence of parents’ PA on their children’s achieving the recommended daily PA is stronger than the inhibitory effect of ST.
Gesehen am 05.05.2020